Ensino médio: Contexto e reforma. afinal, do que se trata? - Ana Luiza Machado de Codes; Sérgio Luiz Doscher da Fonseca; Herton Ellery Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This text aims to analyze the reform of secondary education in Brazil from a specific perspective: the potential to go beyond the traditional task of enabling students to go to university or to become career-ready by offering a broader and more balanced education that prepares them for entry into adult life. When reflecting on its proposals, contents, and feasibility, this study examines the potentialities for the insertion of values and other edifying aspects in the student's life. The potentialities exist, indeed, and the Base Nacional Comum Curricular (BNCC) brings this possibility to the heart of the Reformation. The analysis relies on bibliographic research about models and trends in high school and on international experiences. At the end of the work, some considerations and suggestions aim to help the policy.
Keywords: I28; 330; high school; high school reform in Brazil; preparation for adulthood; school counseling policies